Pengucapan Salam kepada Penganut Agama Lain dalam Perspektif Islam: Antara Etika Sosial dan Prinsip Akidah: Greetings to Followers of Other Religions in an Islamic Perspective: Between Social Ethics and Principles of Faith - Ridwan, Ridwan; Suf Kasman (Litera Academica Publishing, 2025)
The greeting (salam) to followers of other religions in Islam is a form of prayer that aims to bring safety, peace, and mercy. While there are differences of opinion among scholars about whether a Muslim can initiate a greeting to non-Muslims or only respond to it, the fundamental principle of Islam teaches kindness to all of Allah's creatures, including non-Muslims who do not oppose Islam. This study aims to examine the Islamic perspective on greeting followers of other religions, its positive and negative impacts on Islamic da'wah, and to provide strategic recommendations for Muslims in applying interfaith greetings in a harmonious and inclusive manner. The research method employed is a qualitative approach with library research, analyzing the Qur'an, Hadith, and scholars' views on this topic. The results show that interfaith greetings can strengthen social relationships and serve as an effective means of da'wah, as long as it is done with the correct intention and clear understanding. The recommendations include better education on the essence of greeting, the importance of interfaith dialogue, caution in greeting, and the role of scholars in guiding the community to understand and practice interfaith greetings wisely.